Legalisasi Aset Tanah Transmigrasi Dalam Rangka Penguatan Reforma Agraria di Sumatera Utara - Onny Medaline; Juli Moertiono (Jurnal Ilmiah Penegakan Hukum, 2023)
Agrarian reform is a process of rearranging the structure of tenure, ownership, use and utilization of land in a more just manner. Presidential Decree No. 86 of 2018 states that one of the objects of legalization of the assets of the agrarian reform program is uncertified transmigration lands. The complicated problem in legalizing transmigration land is because there are still many remnants of past problems that have not been resolved. This research was conducted to provide an analysis and description of the urgency in implementing the legalization of transmigration land assets in the North Sumatra region in the context of strengthening the agrarian reform program. The type of research used is qualitative research which seeks to find the urgency of implementing legality of transmigration land assets in relation to the agrarian reform program. Based on the letter submitted to the Head of the Workforce and Transmigration Office of North Sumatra Province in 2019, regarding the Data on the Asset Management Program for the Agrarian Reform Task Force (GTRA) activities, there are 5,605 transmigration land areas that have not been certified in North Sumatra Province, spread across 6 regencies. As an object of agrarian reform, the criteria for transmigration land are stated in Presidential Regulation Number 86 of 2018, stating that transmigration land that has not been certified must meet the following criteria: not included in a forest area; or have been granted management rights for transmigration. The conclusion of the regulations governing the legalization of transmigration land assets is an important part of the land certification process which is carried out through land registration.